Treated post-acute sequelae after COVID-19 in a German matched cohort study using routine data from 230,256 adults - Müller, Doreen; Stengel, Sandra; Roesler, Martin; Schillinger, Gerhard; Dräther, Hendrik; Günster, Christian; Tillmanns, Hanna; Erhart, Michael; Szecsenyi, Joachim; Merle, Uta (Frontiers in Epidemiology, 2023)
Background Post-acute sequelae after COVID-19 are still associated with knowledge gaps and uncertainties at the end of 2022, e.g., prevalence, pathogenesis, treatment, and long-term outcomes, and pose challenges for health providers in medical management. The aim of this study was to contribute to the understanding of the multi-faceted condition of long-/ post-COVID. It was designed to evaluate whether a prior SARS-CoV-2 infection during the first COVID-19 wave in Germany increases the rate of disease, as measured via a record of insurance data on diagnoses, symptoms, and treatment, in the subsequent 12 months compared with matched control groups without recorded SARS-CoV-2 infection. Method 50 outcome variables at disease, symptom and treatment levels (14 main categories and 36 sub-categories; new diagnoses) were defined from health insurance data. Logistic regression was carried out for two groups of patients tested positive in a PCR test in March/April 2020 for SARS-CoV-2, compared to the respective risk-adjusted (age, administrative region, 1:5 propensity-score matching), contemporaneous control group without prior documented SARS-CoV-2 infection (CG): First, individuals with outpatient treatment of acute COVID-19, indicating a not severe course (COV-OUT), and second, individuals with inpatient treatment of acute COVID-19, indicating a severe course (COV-IN) were compared with their respective control group. Results The mortality rate in COV-OUT (n = 32,378) and COV-IN (n = 5,998) groups is higher compared to their control groups with odds ratio (OR) 1.5 [95%CI (1.3, 1.6)] and 1.7 [95%CI (1.5, 1.8)] respectively. Both groups were more likely to have experienced at least one outcome compared to their CG [OR = 1.4, 95%CI (1.4, 1.4)]; OR = 2.5, 95%CI [2.4, 2.6]). 42/37 (COV-IN/COV-OUT) outcome variables showed increased ORs. COV-OUT: Loss of taste and smell [OR = 5.8, 95%CI (5.1, 6.6)], interstitial respiratory diseases [OR = 2.8, 95%CI (2.0, 4.1)] and breathing disorders [OR = 3.2, 95%CI (2.2, 4.7)] showed the highest ORs. COV-IN: Interstitial respiratory diseases [OR = 12.2, 95%CI (8.5, 17.5)], oxygen therapy [OR = 8.1, 95%CI (6.4, 10.2)] and pulmonary embolism/anticoagulation [OR = 5.9, 95%CI (4.4, 7.9)] were the most pronounced. Conclusion Following a SARS-CoV-2 infection during the first wave of the COVID-19 pandemic in Germany, 8.4 [COV-OUT, 95%CI (7.7, 9.1)] respectively 25.5 [COV-IN, 95%CI (23.6, 27.4)] percentage points more subjects showed at least one new diagnosis/symptom/treatment compared to their matched CG (COV-OUT: 44.9%, CG: 36.5%; COV-IN: 72.0%, CG: 46.5%). Because the symptoms and diagnoses are so varied, interdisciplinary and interprofessional cooperation among those providing management is necessary.